Exploring impacts and effectiveness of the City of Cape Town’s interventions on household water use practices during the drought - Matikinca, Phikolomzi (Department of Environmental and Geographical Science, 2020)
The occurrence of water crises in many parts of the world raises the need to consider more efficient and sustainable consumption of water resources. As such, many cities have prioritised water demand management strategies, which are based on price and non-price mechanisms. The literature shows no consensus as to which of these measures are most effective for managing residential water demand. To understand the impact and effectiveness of these mechanisms, there is a need to understand how people respond to them. This requires understanding materials, meanings and competences (skills and know how) that people have, which constitute elements of social practice. In 2017 and 2018, the City of Cape Town (CoCT) ramped up their price and non-price mechanisms to encourage people to save water in response to a severe drought. These mechanisms included water restrictions, increased water tariffs, and the Day Zero communication campaign. However, little is known about how effective these measures were at encouraging people to save water. There is no clear documentation of how the public understands, interprets and incorporates these mechanisms into their own household water use practices. This study explores the impacts and effectiveness of the City of Cape Town’s price and non-price mechanisms on household water use practices during the water crisis. Using information obtained through semi-structured interviews with 20 individuals living in houses where they paid their water bills, a version of social practice theory is used as a lens to understand how respondents interpreted and responded to these mechanisms when it comes to residential water use practices. This allows for an assessment of which of the CoCT’s actions are more effective in achieving sustainable water use practices. Results show that price mechanisms (water tariffs) were considered to be ineffective and did not encourage people to save water. Non-price mechanisms (water restrictions and Day Zero communication campaign) were seen as having more impact on respondents, encouraging water conservation behaviour; especially when it comes to household indoor water use activities related to hygiene. Compared to other studies which have used estimates for the water demand function, this study conducted interviews directly with households on the impact of the mechanisms. This enabled this study to explain how and why household water use practices change in response to these measures. Such qualitative information is important and contributes to a field that often uses quantitative data to suggest whether price or non-price mechanisms are effective.